UJI LAYAR RC-MODEL KAPAL BERSAYAP KONFIGURASI SAYAP DAN STEP BERBEDA - syamsuar, sayuti (Badan Pengkajian dan Penerapan Teknologi, 2006)
The remote control (RC) model testing of several configurations of Wing In Surface Effect craft had been beginning from design analysis, technical drawing, aerodynamics wind tunnel, hydrodynamic and RC model test. The mathematical model of Wing In Surface craft is introduced to solve the dynamics problem during takeoff, cruise and landing maneuvres. The theoretical background of hydrodynamic on hull during ground roll calculated by Savitsky method. And the aerodynamic parameters are calculated by Vortex Lattice Method (VLM)5 and DATCOM6 software. The WiSE-craft model flown from lower altitude on the sea level within the speed, V at lower altitude. The wing configurations and step positions of RC models are tested in Jatiluhur to known the dynamic characteristics. One of them is the zig zag manuvre data that recorded by GPS.